Rational Design, Synthesis and In Vitro Activity of Diastereomeric Cis-/Trans-3-Substituted-3,4-Dihydroisocoumarin-4-Carboxylic Acids as Potential Carnitine Acetyltransferase Inhibitors - Savina Stoyanova; Milen G. Bogdanov (Molecules)
This study explores a series of 3,4-dihydroisocoumarins as potential inhibitors of fatty acid oxidation through rational design, synthesis and in vitro evaluation. The compounds studied were designed as structural analogs of the natural substrates of carnitine acetyltransferase (CAT) and other enzymes in the carnitine transferase family, which play a crucial role in fatty acid metabolism. Comparative in vitro analyses revealed that the presence of an alkyl substituent at position 3 of the heterocyclic core, along with its chain length, significantly influences inhibitory activity, yielding IC50 values in the micromolar range. Kinetic studies of one of the most potent compounds—cis- and trans-3-decyl-6,7-dimethoxy-3,4-dihydroisocoumarin-4-carboxylic acids—demonstrated mixed inhibition of CAT, with Ki values of 130 μM and 380 μM, respectively. These findings underscore the therapeutic potential of the compounds under investigation in modulating fatty acid catabolism, with possible applications in treating metabolic disorders.